Blast shock wave attenuation in square cross-sectional truss based meso-scale lattice architectures. (October 2022) - Ye, Jiayi; Zhang, Yuwu; Li, Yugang; Wang, Qingtao
Abstract: With the rapid growth in defense and civilian industry interests, high-performance materials like lattice materials capable of resisting high strain-rate loads are urgently required. Researchers mainly focus on the irreversible plastic deformation of lattice core sandwich structures under out-of-plane loads, whereas the potential application of cellular core without sandwiched face sheets has not been explored. In fact, when shock waves directly act on a cellular core without sandwiched face sheet, the energy would be consumed in the voids during the wave propagation. This article gives an insight into the shock wave attenuation characteristics and the attenuation mechanisms of square cross-sectional truss based meso -scale lattice architectures. Two types of lattice configurations with the same porosity but different truss sectional arrangements are employed. It is reported that both types of the lattice architectures can considerably dissipate the shock wave. The variation trends of overpressure-time history for the meso -scale lattice architectures are significantly different from those obtained in the free air field. As the truss-sectional size decreases the detected first peak overpressure decreases and becomes gradually lower than the second peak overpressure due to the increasing truss layers. When the edge length of truss section, d, decreases from 0.4 mm to 0.1 mm at a constant scaled distance of 0.896, the attenuation efficiency of the peak overpressure is increased by 30 % to 70 %, and the efficiency of the impulse is increased by 60 %, together with a highly-improved increasing rate for the delaying efficiency of the arrival time. Considering distinct scaled distances, the type II architecture and type I architecture behave superiorly with respect to the attenuation efficiencies of peak overpressure and impulse, respectively. Compared to the free field scenario, a shorter wave propagation distance could be observed for the meso -scale lattice architectures to achieve the same peak overpressure and impulse. The considerable shock wave attenuation of the meso -scale lattice architecture is attributed to the complex interactions of the shock wave reflection, diffraction, and superposition around the truss sections and in the voids. This investigation provides a novel method for the shock wave attenuation and energy consumption to protect vital targets and precise equipment.